2018
DOI: 10.1002/cctc.201801008
|View full text |Cite
|
Sign up to set email alerts
|

Olefin Polymerization Reactivity of Group 4 Post‐Metallocene Catalysts Bearing a Four‐Membered C(sp3)‐Donor Chelate Ring

Abstract: The synthesis, spectroscopic and structural characterization, and olefin polymerization behavior of a family of pyridine‐2‐phenolate‐6‐arylmethine [O,N,CH(Ar)] Group 4 catalysts bearing a four‐membered N,C(sp3)‐donor metallacycle are described. The racemic [O,N,CH(Ar)] complexes adopt C1 symmetry, as confirmed by NMR spectroscopy and X‐ray crystallography. Advanced NMR experiments have been conducted to probe for possible C−H⋅⋅⋅F−C interactions within fluorinated derivatives. Use of a bis‐pyridyl ligand (Ar=py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…By performing anionic polymerization of styrene in a one-pot reaction after CCTP with I , it is also possible to synthesize polyolefin-polystyrene block copolymers [23,24,25]. In this context, many studies have been performed to detail I and to improve the catalytic performance by modifying the skeleton of I [26,27,28,29,30,31,32,33,34,35]. With an aim to develop upgraded catalyst for I , we prepared various pincer-type Hf-complexes.…”
Section: Introductionmentioning
confidence: 99%
“…By performing anionic polymerization of styrene in a one-pot reaction after CCTP with I , it is also possible to synthesize polyolefin-polystyrene block copolymers [23,24,25]. In this context, many studies have been performed to detail I and to improve the catalytic performance by modifying the skeleton of I [26,27,28,29,30,31,32,33,34,35]. With an aim to develop upgraded catalyst for I , we prepared various pincer-type Hf-complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Attention is drawn to the conformation of the benzyl moieties, which typically extend outward and away from the tridentate ligand in related group 4 postmetallocene complexes (as is the case for the Ti derivatives herein, according to ROESY experiments). 4,14,22,34 Here, the severely distorted "quasi-meridional" coordination evident in 8 causes the η 2 -coordinated benzyl group (C34−C40) to "wrap" around the σ-aryl unit (without π-stacking) so that the Zr−benzyl linkages and the alignment of the benzyl moieties are virtually perpendicular (torsional angle between C27−C28 and C34−C35 = 95.8°). Consequently, the shortest distance between the CH 2 (benzyl) and shown in Figure S4 for 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…8,9 Our initial studies 10,11 revealed that Ti-[O,N,C] catalysts can produce polyolefins with high M w /M n values suggestive of multisite behavior, which was subsequently ascribed to facile olefin insertion into the Ti− C(σ-aryl) bond to afford supplementary "olefin-assimilated" active species, 12 and efforts have been undertaken to modify and ameliorate polymerization characteristics. 13,14 The corresponding 2-arylamido [N,N,C]-Hf catalysts were developed by Symyx and Dow through the use of highthroughput screening, 15,16 and the analogous olefin insertion into the M−C(σ-aryl) bond of these 17,18 and related 19,20 Zr derivatives to generate olefin-assimilated (or "monomerinserted") active sites have been reported. Inspired by this unusual insertion reaction, Coates et al designed pyridylamido 21 and phenolate-amine 22 ligands bearing a pendant vinyl moiety, 23 which undergo metalation with group 4 alkyl species to afford C(sp 3 )-chelating catalysts that mediate the living isoselective polymerization of α-olefins.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also demonstrated that the CCTP involving III , could be switched to anionic styrene polymerization to prepare polyolefin-polystyrene block copolymers [11,20,21,22]. In this context, many thorough studies have been performed to detail III , and to improve the catalytic activity by modifying its ligand skeleton [23,24,25,26,27,28,29,30,31,32]. To develop an upgraded catalyst relative to III , we prepared various Hf complexes.…”
Section: Introductionmentioning
confidence: 99%